Safe Haskell | Safe |
---|---|

Language | Haskell98 |

- (<$$>) :: (Functor f0, Functor f1) => (a -> b) -> f1 (f0 a) -> f1 (f0 b)
- (<$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b) -> f2 (f1 (f0 a)) -> f2 (f1 (f0 b))
- (<$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b) -> f3 (f2 (f1 (f0 a))) -> f3 (f2 (f1 (f0 b)))
- (<$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b) -> f4 (f3 (f2 (f1 (f0 a)))) -> f4 (f3 (f2 (f1 (f0 b))))
- (<$~>) :: Functor f0 => f0 (a -> b) -> a -> f0 b
- (<~$>) :: Functor f0 => (a -> b -> c) -> f0 b -> f0 (a -> c)
- (<$~~>) :: Functor f0 => f0 (a -> b -> c) -> b -> f0 (a -> c)
- (<~~$>) :: Functor f0 => (a -> b -> c -> d) -> f0 c -> f0 (a -> b -> d)
- (<$~~~>) :: Functor f0 => f0 (a -> b -> c -> d) -> c -> f0 (a -> b -> d)
- (<~~~$>) :: Functor f0 => (a -> b -> c -> d -> e) -> f0 d -> f0 (a -> b -> c -> e)
- (<$$~>) :: (Functor f0, Functor f1) => f1 (f0 (a -> b)) -> a -> f1 (f0 b)
- (<~$$>) :: (Functor f0, Functor f1) => (a -> b -> c) -> f1 (f0 b) -> f1 (f0 (a -> c))
- (<$$~~>) :: (Functor f0, Functor f1) => f1 (f0 (a -> b -> c)) -> b -> f1 (f0 (a -> c))
- (<~~$$>) :: (Functor f0, Functor f1) => (a -> b -> c -> d) -> f1 (f0 c) -> f1 (f0 (a -> b -> d))
- (<$$~~~>) :: (Functor f0, Functor f1) => f1 (f0 (a -> b -> c -> d)) -> c -> f1 (f0 (a -> b -> d))
- (<~~~$$>) :: (Functor f0, Functor f1) => (a -> b -> c -> d -> e) -> f1 (f0 d) -> f1 (f0 (a -> b -> c -> e))
- (<$$$~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b))) -> a -> f2 (f1 (f0 b))
- (<~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c) -> f2 (f1 (f0 b)) -> f2 (f1 (f0 (a -> c)))
- (<$$$~~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b -> c))) -> b -> f2 (f1 (f0 (a -> c)))
- (<~~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c -> d) -> f2 (f1 (f0 c)) -> f2 (f1 (f0 (a -> b -> d)))
- (<$$$~~~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b -> c -> d))) -> c -> f2 (f1 (f0 (a -> b -> d)))
- (<~~~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c -> d -> e) -> f2 (f1 (f0 d)) -> f2 (f1 (f0 (a -> b -> c -> e)))
- (<$$$$~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b)))) -> a -> f3 (f2 (f1 (f0 b)))
- (<~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c) -> f3 (f2 (f1 (f0 b))) -> f3 (f2 (f1 (f0 (a -> c))))
- (<$$$$~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b -> c)))) -> b -> f3 (f2 (f1 (f0 (a -> c))))
- (<~~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c -> d) -> f3 (f2 (f1 (f0 c))) -> f3 (f2 (f1 (f0 (a -> b -> d))))
- (<$$$$~~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b -> c -> d)))) -> c -> f3 (f2 (f1 (f0 (a -> b -> d))))
- (<~~~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c -> d -> e) -> f3 (f2 (f1 (f0 d))) -> f3 (f2 (f1 (f0 (a -> b -> c -> e))))
- (<$$$$$~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b))))) -> a -> f4 (f3 (f2 (f1 (f0 b))))
- (<~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c) -> f4 (f3 (f2 (f1 (f0 b)))) -> f4 (f3 (f2 (f1 (f0 (a -> c)))))
- (<$$$$$~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b -> c))))) -> b -> f4 (f3 (f2 (f1 (f0 (a -> c)))))
- (<~~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c -> d) -> f4 (f3 (f2 (f1 (f0 c)))) -> f4 (f3 (f2 (f1 (f0 (a -> b -> d)))))
- (<$$$$$~~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b -> c -> d))))) -> c -> f4 (f3 (f2 (f1 (f0 (a -> b -> d)))))
- (<~~~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c -> d -> e) -> f4 (f3 (f2 (f1 (f0 d)))) -> f4 (f3 (f2 (f1 (f0 (a -> b -> c -> e)))))
- (<.$>) :: Functor f0 => (b -> c) -> f0 (a -> b) -> f0 (a -> c)
- (<.*$>) :: Functor f0 => (c -> d) -> f0 (a -> b -> c) -> f0 (a -> b -> d)
- (<*.$>) :: Functor f0 => (a -> c -> d) -> f0 (b -> c) -> f0 (a -> b -> d)
- (<.**$>) :: Functor f0 => (d -> e) -> f0 (a -> b -> c -> d) -> f0 (a -> b -> c -> e)
- (<.$$>) :: (Functor f0, Functor f1) => (b -> c) -> f1 (f0 (a -> b)) -> f1 (f0 (a -> c))
- (<.*$$>) :: (Functor f0, Functor f1) => (c -> d) -> f1 (f0 (a -> b -> c)) -> f1 (f0 (a -> b -> d))
- (<.**$$>) :: (Functor f0, Functor f1) => (d -> e) -> f1 (f0 (a -> b -> c -> d)) -> f1 (f0 (a -> b -> c -> e))
- (<.$$$>) :: (Functor f0, Functor f1, Functor f2) => (b -> c) -> f2 (f1 (f0 (a -> b))) -> f2 (f1 (f0 (a -> c)))
- (<.*$$$>) :: (Functor f0, Functor f1, Functor f2) => (c -> d) -> f2 (f1 (f0 (a -> b -> c))) -> f2 (f1 (f0 (a -> b -> d)))
- (<.**$$$>) :: (Functor f0, Functor f1, Functor f2) => (d -> e) -> f2 (f1 (f0 (a -> b -> c -> d))) -> f2 (f1 (f0 (a -> b -> c -> e)))
- (<.$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (b -> c) -> f3 (f2 (f1 (f0 (a -> b)))) -> f3 (f2 (f1 (f0 (a -> c))))
- (<.*$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (c -> d) -> f3 (f2 (f1 (f0 (a -> b -> c)))) -> f3 (f2 (f1 (f0 (a -> b -> d))))
- (<.**$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (d -> e) -> f3 (f2 (f1 (f0 (a -> b -> c -> d)))) -> f3 (f2 (f1 (f0 (a -> b -> c -> e))))

# Nested Mapping

(<$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b) -> f2 (f1 (f0 a)) -> f2 (f1 (f0 b)) infixr 8 Source

(<$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b) -> f3 (f2 (f1 (f0 a))) -> f3 (f2 (f1 (f0 b))) infixr 8 Source

(<$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b) -> f4 (f3 (f2 (f1 (f0 a)))) -> f4 (f3 (f2 (f1 (f0 b)))) infixr 8 Source

# Nested Application

(<~$$>) :: (Functor f0, Functor f1) => (a -> b -> c) -> f1 (f0 b) -> f1 (f0 (a -> c)) infixr 8 Source

(<$$~~>) :: (Functor f0, Functor f1) => f1 (f0 (a -> b -> c)) -> b -> f1 (f0 (a -> c)) infixl 8 Source

(<~~$$>) :: (Functor f0, Functor f1) => (a -> b -> c -> d) -> f1 (f0 c) -> f1 (f0 (a -> b -> d)) infixr 8 Source

(<$$~~~>) :: (Functor f0, Functor f1) => f1 (f0 (a -> b -> c -> d)) -> c -> f1 (f0 (a -> b -> d)) infixl 8 Source

(<~~~$$>) :: (Functor f0, Functor f1) => (a -> b -> c -> d -> e) -> f1 (f0 d) -> f1 (f0 (a -> b -> c -> e)) infixr 8 Source

(<$$$~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b))) -> a -> f2 (f1 (f0 b)) infixl 8 Source

(<~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c) -> f2 (f1 (f0 b)) -> f2 (f1 (f0 (a -> c))) infixr 8 Source

(<$$$~~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b -> c))) -> b -> f2 (f1 (f0 (a -> c))) infixl 8 Source

(<~~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c -> d) -> f2 (f1 (f0 c)) -> f2 (f1 (f0 (a -> b -> d))) infixr 8 Source

(<$$$~~~>) :: (Functor f0, Functor f1, Functor f2) => f2 (f1 (f0 (a -> b -> c -> d))) -> c -> f2 (f1 (f0 (a -> b -> d))) infixl 8 Source

(<~~~$$$>) :: (Functor f0, Functor f1, Functor f2) => (a -> b -> c -> d -> e) -> f2 (f1 (f0 d)) -> f2 (f1 (f0 (a -> b -> c -> e))) infixr 8 Source

(<$$$$~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b)))) -> a -> f3 (f2 (f1 (f0 b))) infixl 8 Source

(<~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c) -> f3 (f2 (f1 (f0 b))) -> f3 (f2 (f1 (f0 (a -> c)))) infixr 8 Source

(<$$$$~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b -> c)))) -> b -> f3 (f2 (f1 (f0 (a -> c)))) infixl 8 Source

(<~~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c -> d) -> f3 (f2 (f1 (f0 c))) -> f3 (f2 (f1 (f0 (a -> b -> d)))) infixr 8 Source

(<$$$$~~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => f3 (f2 (f1 (f0 (a -> b -> c -> d)))) -> c -> f3 (f2 (f1 (f0 (a -> b -> d)))) infixl 8 Source

(<~~~$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (a -> b -> c -> d -> e) -> f3 (f2 (f1 (f0 d))) -> f3 (f2 (f1 (f0 (a -> b -> c -> e)))) infixr 8 Source

(<$$$$$~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b))))) -> a -> f4 (f3 (f2 (f1 (f0 b)))) infixl 8 Source

(<~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c) -> f4 (f3 (f2 (f1 (f0 b)))) -> f4 (f3 (f2 (f1 (f0 (a -> c))))) infixr 8 Source

(<$$$$$~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b -> c))))) -> b -> f4 (f3 (f2 (f1 (f0 (a -> c))))) infixl 8 Source

(<~~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c -> d) -> f4 (f3 (f2 (f1 (f0 c)))) -> f4 (f3 (f2 (f1 (f0 (a -> b -> d))))) infixr 8 Source

(<$$$$$~~~>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => f4 (f3 (f2 (f1 (f0 (a -> b -> c -> d))))) -> c -> f4 (f3 (f2 (f1 (f0 (a -> b -> d))))) infixl 8 Source

(<~~~$$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3, Functor f4) => (a -> b -> c -> d -> e) -> f4 (f3 (f2 (f1 (f0 d)))) -> f4 (f3 (f2 (f1 (f0 (a -> b -> c -> e))))) infixr 8 Source

# Nested Compositon

(<.**$>) :: Functor f0 => (d -> e) -> f0 (a -> b -> c -> d) -> f0 (a -> b -> c -> e) infixr 8 Source

(<.$$>) :: (Functor f0, Functor f1) => (b -> c) -> f1 (f0 (a -> b)) -> f1 (f0 (a -> c)) infixr 8 Source

(<.*$$>) :: (Functor f0, Functor f1) => (c -> d) -> f1 (f0 (a -> b -> c)) -> f1 (f0 (a -> b -> d)) infixr 8 Source

(<.**$$>) :: (Functor f0, Functor f1) => (d -> e) -> f1 (f0 (a -> b -> c -> d)) -> f1 (f0 (a -> b -> c -> e)) infixr 8 Source

(<.$$$>) :: (Functor f0, Functor f1, Functor f2) => (b -> c) -> f2 (f1 (f0 (a -> b))) -> f2 (f1 (f0 (a -> c))) infixr 8 Source

(<.*$$$>) :: (Functor f0, Functor f1, Functor f2) => (c -> d) -> f2 (f1 (f0 (a -> b -> c))) -> f2 (f1 (f0 (a -> b -> d))) infixr 8 Source

(<.**$$$>) :: (Functor f0, Functor f1, Functor f2) => (d -> e) -> f2 (f1 (f0 (a -> b -> c -> d))) -> f2 (f1 (f0 (a -> b -> c -> e))) infixr 8 Source

(<.$$$$>) :: (Functor f0, Functor f1, Functor f2, Functor f3) => (b -> c) -> f3 (f2 (f1 (f0 (a -> b)))) -> f3 (f2 (f1 (f0 (a -> c)))) infixr 8 Source